2020
DOI: 10.12788/jhm.3381
|View full text |Cite
|
Sign up to set email alerts
|

The History of Pediatric Hospital Medicine in the United States, 1996‐2019

Abstract: coined the term "hospitalist" and predicted an "emerging role in the American health care system." 1 Pediatrics was not far behind: In 1999, Dr Wachter joined Paul Bellet, MD, in authoring an article describing the movement within pediatrics. 2 An accompanying editorial, coauthored by a pediatric hospitalist and an office-based practitioner, attempted to answer which was "better" for a hospitalized child: A practitioner who knew the child and family or a hospitalist who might be more knowledgeable about the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…Over the last 20 years, the field of Pediatric Hospital Medicine (PHM) has been steadily growing and evolving. Historically, outpatient pediatricians followed their patients both in and out of the hospital [ 1 ]; however, a 2012 American Academy of Pediatrics survey showed that outpatient pediatricians are the inpatient attending for less than one-third of admitted patients from their practice [ 2 ]. Hospitalist services continue to expand and now dominate in large children’s hospitals, with 98% of hospitals associated with academic pediatric departments reporting dedicated PHM hospitalist services [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 20 years, the field of Pediatric Hospital Medicine (PHM) has been steadily growing and evolving. Historically, outpatient pediatricians followed their patients both in and out of the hospital [ 1 ]; however, a 2012 American Academy of Pediatrics survey showed that outpatient pediatricians are the inpatient attending for less than one-third of admitted patients from their practice [ 2 ]. Hospitalist services continue to expand and now dominate in large children’s hospitals, with 98% of hospitals associated with academic pediatric departments reporting dedicated PHM hospitalist services [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 PHM fellowships, the first 3 of which were initiated in the United States in 2003, were developed in response to the growing complexity of hospitalized children and the knowledge that hospitalists play a key role in medical education, quality improvement (QI), care coordination, health informatics, scholarly activity, and more, much of which is not formally taught in residency. [4][5][6] The American Board of Pediatrics approved subspecialty status for PHM in December 2015, and the American Board of Medical Specialties later approved it in October 2016. There are now .30 PHM fellowship programs accredited by the Accreditation Council for Graduate Medical Education (ACGME) and .60 total programs in existence.…”
mentioning
confidence: 99%
“…In addition, the requirement to complete a PHM fellowship to become board certified in PHM may disproportionately affect Combined Internal Medicine and Pediatric (Med-Peds) practitioners, who make up an estimated 10% of the PHM workforce. 4,11,12 More than 80% of Med-Peds practitioners see both adults and children, and of these practitioners, .90% feel their training prepared them to practice in both age groups. 12 These reservations regarding delay in full-time salary achievement and impact on Med-Peds practitioners have been previously discussed in a 2016 survey of members of the Association of Medical School Pediatric Department Chairs, where only 16% of pediatric chairs supported a PHM board certification requirement.…”
mentioning
confidence: 99%
“…The modern history of PHM has recently been reviewed. 22 Changes in graduate medical education figured prominently in promoting the predicted "emerging role" for hospitalists. In the late 1990s, Medicare reissued Intermediary Letter 372 requiring attending physicians to document that they had personally performed services to patients beyond those of residents; supervising residents and cosigning their notes were no longer sufficient.…”
Section: Hospital Medicine Emergesmentioning
confidence: 99%